The IMPACT OF CURICULUM DEVELOPMENT IN THE COGNTIVE DOMAIN AND THE PERFORMMANCE OF SOM HANDBALL BASIC SKILLS FOR STUDIENTS OF PHYSICAL EDUCACION - KHAMEES , AHMED (Journal of Physical Education, 2012)
The research aims to prepare the curriculum for the development of the cognitive domain and the performance of some handball basic skills for students of physical education. The second objective was to identify the differences between tribal and post tests in the development of the cognitive domain and the performance of some basic skills, The third objective was to identify the relationship between cognitive domain and the performance of some handball basic skills of students of physical education.The first hypothesis was: There are statistically significant differences between the results of tests of tribal and post in the In the evolution of the cognitive domain and the performance of some basic skills in handball of students of physical education., and the second hypothesis that there is a correlation between cognitive domain and the performance of some handball basic skills of students of physical education.The researcher used the experimental method designed with one group pre-testing and post the sample consisted of (15) Students from the Department of Health and recreation for the season 2010-2011 academic, Where the subject group of the curriculum by two units a week, has conducted a researcher tests tribal before the implementation of the curriculum after the specified form, measure the area of knowledge and skills tests basic handball, has returned tests after completion of the training curriculum, and was processing the results statistically by the use of the bag the SPSS statistical system. The main conclusions were: that the field of cognitive major role in the performance level of basic skills for students of Physical Education, and after presentation of the conclusions the researcher provided a set of recommendations including the need for familiarity with the teacher tactics of knowledge possessed by students to their importance in achieving better results in learning knowledge and skills.